2015
DOI: 10.1007/s12603-014-0559-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leucine-rich protein supplements on anthropometric parameter and muscle strength in the elderly: A systematic review and meta-analysis

Abstract: It is concluded that leucine supplementation was found to exert beneficial effects on body weight, body mass index, and lean body mass in older persons in those subjects already prone to sarcopenia, but not muscle strength. However, due to the heterogeneity between the trials included in this systematic review, further studies adopting a homogenous design with respect to participant characteristics duration as well as the kind and amount of daily supplement in use are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 64 publications
2
91
1
7
Order By: Relevance
“…In addition, when a difference is evidenced in an older adult, should alert of possible osteoporosis (21, 10, 3, 11) and may point to the fact that the BMI (and other body composition parameters) should be calculated with the estimated value rather than with the measured one, because of overestimation of obesity (or missing low weight) in older adults or misclassification that could lead to restrictive diets (22) or other treatments (23). Testing this difference in clinical setting and research could also help in advancing the field of so-called osteo-sarcopenia (24), giving a practical measurement that could be added to calf circumference measurement (25) to test this problem in every-day care; however this is still to be clarified in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when a difference is evidenced in an older adult, should alert of possible osteoporosis (21, 10, 3, 11) and may point to the fact that the BMI (and other body composition parameters) should be calculated with the estimated value rather than with the measured one, because of overestimation of obesity (or missing low weight) in older adults or misclassification that could lead to restrictive diets (22) or other treatments (23). Testing this difference in clinical setting and research could also help in advancing the field of so-called osteo-sarcopenia (24), giving a practical measurement that could be added to calf circumference measurement (25) to test this problem in every-day care; however this is still to be clarified in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Consistent with recent reviews,[23,24] we also used 1.0 g/kg body weight as the cutoff for meeting protein recommendations, but there were no substantive differences with respect to associations with body composition measures. Trials administering protein supplements enriched in specific amino acids, such as leucine [25] and cysteine[26], suggest focusing on the protein quality as well as quantity may be important in future work.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term effect of leucine supplementation on body composition has been assessed largely in selected physiological conditions such as exercise, malnutrition, or aging, all situations where protein metabolism is challenged, and both positive and no effects have been reported (5,14,27,37,71,80). A recent meta-analysis concluded that leucine supplementation exerts beneficial effects on body weight and lean body mass in older persons already prone to sarcopenia (49). Beneficial effects on lean body mass and/or muscle mass in rats (11) and humans (7,24) have also been reported with supplementation of leucineenriched amino acid mixtures.…”
Section: E706 Leucine Pulses Increase Lean Gain In Neonatesmentioning
confidence: 99%